Кооптація запорозької старшини до дворянства у законодавчій практиці Російської Iмперії. (Zaporizhzhia Historical Review, 2021)
The nobilitation of Zaporizhzhyan starshyna to the gentry of Russian Empire is being analysed. It is demonstrated that this process had electoral and consecutive character and was based upon the personal relationship and intercession.